Microwave assisted thermal process of castor oil for the production of specialty chemical - J., Sazali (2018)
The utilization of vegetable oils is currently in the highlight of the chemical industry, as they are one of the most important renewable resources due to their universal availability, inherent biodegradability, low price, and eco-friendly. Castor oil from castor plant (Ricinus Communis) which is the non-edible oil crop is chosen in this study due to the high annual seed production and yield, and since it can be grown on marginal land and in semi-arid climate [1]. Castor oil derivatives are variously used in the production of paints, varnishes, coatings, lubricants and grease, hydraulic fluids, soaps, printing inks, and as a raw material in the manufacturing of various chemicals [2]. The chemistry of castor oil is centered on its high percentage of 12-hydroxy-9-octadecenoic acid (ricinoleic acid) and the three types of functionality existing in the molecule. These are the carboxyl group which can provide a wide range of esterifications; the single point of unsaturation which can be altered by hydrogenation or epoxidation or vulcanization; and the hydroxyl group which can be acetylated or alkoxylated, may be removed by dehydration to increase the unsaturation of the compound to give a semi-drying oil.